Bridging Home and School: Communication Management Strategies of Islamic Institution for Fatherless Children - Nanin Lutfiani (Journal of Educational Management Research, 2025)
This study aims to examine how Islamic educational institutions manage communication with single-parent families to support family-based Islamic education for fatherless children. Fatherlessness has become an urgent social and educational issue because the absence of paternal involvement may weaken children’s moral guidance, emotional security, and religious value formation. In Islamic educational contexts, this condition requires structured school–family collaboration to sustain character education beyond the classroom. This study employed a qualitative case study design in three Islamic educational institutions in Indonesia. Data were collected through semi-structured interviews, participatory observation, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The first finding shows that intensive value-based communication enables schools to monitor children’s behavioral and religious development. The second finding reveals that participatory parental engagement strengthens single mothers’ parenting capacity through consultation, religious programs, and character guidance. The third finding indicates that value synchronization between school and home functions as a moral contract for character formation. These findings contribute to Islamic educational management by proposing an adaptive communication–education partnership model. Practically, the study offers guidance for schools in supporting fatherless children and single-parent families.